GENERASI MILLENNIAL DAN INOVASI JEJARING DEMOKRASI TEMAN AHOK - Retnayu Prasetyanti (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2017)
Millennial generation nowadays prominently inspires innovation not only in the development of technology and knowledge but also in the social and political arena. In this fast-changing era, the world can’t resist the trend of digital application and its dissimilar impacts on various realms. Millennial generation, somehow, hit by adverse impacts of the development of technology based digital application; however in another side, this Y generation also gives significant influences on political dynamism in Jakarta. Millennial generation movement known as TEMAN AHOK: a community which supports Ahok to be Independent Candidate of Jakarta Governor 2017 defined as a new trend of political innovation pioneered by millennial generation. By developing a qualitative research as its methodological framework, this research tried to describe the role of millennial generation in managing political network and enhancing democracy. This study also elaborates the expanded effects of millennial generation participation on future political development and policy formulation process in Jakarta and Indonesia. The existence of TEMAN AHOK has been assumed as a critic for government to redefined democracy as a whole process from people, by people, and for people, not from political party, by political party, and for political party.